Short-term Tolerance to Inhaled Antibiotics in Patients With Bronchial Infection not Associated With Cystic Fibrosis - Luis Máiz; Rosa Nieto; Diego Durán; José Máiz; Gabriel Ruiz-Calvo; Alfonso Muriel; Esther Barbero; Manuel Vélez-Díaz-Pallarés; Raquel Morillo (Open Respiratory Archives)
Introduction: The use of intravenous antibiotic formulations delivered by inhalation is controversial. Tolerance can be an issue and some treatment guidelines discourage this route of administration if the same antibiotic is available in an inhalation formulation. Material and methods: This was a retrospective, observational, single-center study comparing tolerance to three antibiotics delivered by nebulization (intravenous formulations of ampicillin and gentamicin, and an inhalation formulation of colistimethate sodium) in patients with bronchial infection (BI), chronic bronchial infection (CBI), and/or recurrent respiratory infections. The study also aimed to identify factors potentially associated with tolerability. Results: A total of 330 antibiotic tolerance tests were performed in 135 patients (mean age 68 years; 48.9% female; mean post-bronchodilator FEV1% predicted 65.9%). Of these patients, 62.2% had bronchiectasis and 39.3% had chronic obstructive pulmonary disease (COPD). The best tolerated antibiotic was colistimethate. Overall, 89.6% of colistimethate doses were tolerated, compared to 69.5% of inhaled gentamicin doses (P < 0.001) and 69.1% of ampicillin doses (P < 0.001). Compared with colistimethate administration, the odds of intolerance were 5.69 times higher for gentamicin (P < 0.001) and 6.21 times higher for ampicillin (P < 0.001). In the univariate analysis, factors that may have been associated with antibiotic intolerance included smoking habit, worse post-bronchodilator FEV1% predicted and a diagnosis of COPD. In the multivariate analysis, after adjustment for antibiotic type, smoking habit, post-bronchodilator FEV1 and COPD diagnosis, the only factor influencing tolerance was the type of antibiotic used. Conclusion: In patients with BI and/or CBI and/or recurrent respiratory infections, inhaled sodium colistimethate is significantly better tolerated than intravenous formulations of gentamicin and ampicillin for the inhalation route. The only factor influencing tolerance is the type of antibiotic used. Resumen: Introducción: La utilización de formulaciones de antibióticos por vía inhalada es controvertida. Algunas normativas desaconsejan su empleo si el mismo antibiótico está disponible en formulaciones específicas para inhalación. Material y métodos: Estudio retrospectivo, observacional y unicéntrico en pacientes sometidos a pruebas de tolerancia a tres antibióticos inhalados. Se comparó la tolerancia a la ampicilina, la gentamicina y el colistimetato sódico inhalados en pacientes con infección bronquial (IB) y/o infección bronquial crónica (IBC) y/o infecciones respiratorias recurrentes. Además, el estudio pretendía identificar los factores potencialmente asociados a la tolerabilidad. Resultados: Se realizaron 330 pruebas de tolerancia a los antibióticos en 135 pacientes (edad media: 68 años; 48,9% mujeres; media del FEV1 postbroncodilatador % predicho = 65,9%). El 62,2% de los pacientes tenían bronquiectasias, y el 39,3%, enfermedad pulmonar obstructiva crónica (EPOC). El antibiótico mejor tolerado fue el colistimetato. Se toleraron el 89,6% de las dosis de colistimetato, en comparación con el 69,5% de las de gentamicina inhalada (p < 0,001) y el 69,1% de las de ampicilina (p < 0,001). La probabilidad de no tolerar gentamicina y ampicilina fue, respectivamente, 5,69 y 6,21 veces mayor que la probabilidad de tolerar colistimetato (p < 0,001). En el análisis univariante, los factores que se asociaron con intolerancia a los antibióticos fueron el hábito tabáquico, un peor FEV1 postbroncodilatador % predicho y el diagnóstico de EPOC. En el análisis multivariante, tras ajustar por tipo de antibiótico, hábito tabáquico, FEV1 postbroncodilatador y diagnóstico de EPOC, el único factor que influyó en la tolerancia fue el tipo de antibiótico utilizado. Conclusión: En pacientes con IB y/o IBC y/o infecciones respiratorias de repetición el colistimetato de sodio inhalado se tolera significativamente mejor que las formulaciones intravenosas de gentamicina y ampicilina empleadas por vía inhalada. El único factor que influye en la tolerancia es el tipo de antibiótico utilizado.